2007
DOI: 10.1002/masy.200751409
|View full text |Cite
|
Sign up to set email alerts
|

Propylene Copolymers with Odd Carbon Number Olefins

Abstract: Preliminary investigation on propylene copolymers with odd carbon number olefin are reviewed. Additional experimental data presents propylene copolymers with 1‐heptene and 1‐nonene having higher impact strength and lower tensile strength values than copolymers of propylene and 1‐pentene.Thermoanalysis shows that the melting temperatures of the different copolymers decreases with increasing comonomer content. Slight changes were observed between the different propylene/1‐heptene copolymer melting and propylene/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…[ 33–36 ] However, the use of olefins with an odd number of carbons has been rather neglected. [ 37,38 ] It was found that the impact strength in different copolymers (1‐pentene, 1‐heptene, and 1‐nonene) is dependent, as expected, on comonomer content, but also on its length. Those incorporating 1‐nonene as counit show higher values of impact strength, at smaller comonomer compositions, than those exhibited by their homologues with 1‐pentene and 1‐heptene.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…[ 33–36 ] However, the use of olefins with an odd number of carbons has been rather neglected. [ 37,38 ] It was found that the impact strength in different copolymers (1‐pentene, 1‐heptene, and 1‐nonene) is dependent, as expected, on comonomer content, but also on its length. Those incorporating 1‐nonene as counit show higher values of impact strength, at smaller comonomer compositions, than those exhibited by their homologues with 1‐pentene and 1‐heptene.…”
Section: Introductionmentioning
confidence: 57%
“…Moreover, it was also found in propylene copolymers that impact strength does not start increasing immediately, as observed for the ethylene copolymers, [39] but the rise is more gradual and follows an exponential increase with comonomer content. [38] More recently, the interest in the copolymers or terpolymers of propylene with 1-pentene or 1-heptene was concentrated primarily on the ability of developing the new trigonal crystalline lattice, as mentioned above, [19][20][21][22]27,28] but there are not systematic studies on microstructure and crystalline characteristics for copolymers with 1-nonene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1‐octene is the comonomer of choice in the manufacture of LLDPEs as it gives a mechanically better product as compared to other even‐numbered 1‐olefins. Considering the high demand of 1‐olefins for LLDPE production and the recently observed global shortage of 1‐octene, odd numbered Fischer‐Tropsch‐derived 1‐olefins such as 1‐pentene and 1‐heptene can be interesting alternatives to 1‐hexene and 1‐octene, respectively. Furthermore, the microstructures of LLDPEs made from the odd‐numbered 1‐olefins may be closely related to those made from even‐numbered 1‐olefins of comparable molar mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few works on ethylene‐1‐pentene and propylene‐1‐pentene copolymers and to our knowledge any work on ethylene‐propylene‐1‐pentene terpolymers. Ethylene‐1‐pentene copolymers have been studied concerning their chemical distribution14 and thermal, crystallization, and reological properties15 and propylene‐1‐pentene random copolymers having high impact strength, good tensile and reological properties, excellent optical properties and a large processing window have been prepared 16. The 13 C NMR spectroscopy is the most successful analytical tool to study molecular structure of polymers and allows researchers to obtain comonomer sequences, short‐chain and long‐chain branch distributions, and quantitative analyses of the composition 17, 18.…”
Section: Introductionmentioning
confidence: 99%